The Theory of Investment and Production - Smith, Vernon L. (Quarterly Journal of Economics, 1959)
I. Introduction, contributions to investment theory, 61. — II. Capital inputs in production theory, 62. — III. Production, using capital goods, with a fixed replacement policy, 66. — IV. Replacement theory, 72. — V. A theory of investment, replacement, and production, 77. — VI. “Overcapacity” and the dynamics of production, 80.— VII. Investment demand and the “acceleration principle,” 83. — VIII. Summary, 86.